2017
DOI: 10.1186/s40623-017-0656-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of newly refined hypocenter locations on the seismic activity recorded during the 2016 Kumamoto Earthquake sequence

Abstract: We present the results of relocating 17,544 hypocenters determined from data recorded during the 2016 Kumamoto Earthquake sequence, during the interval between April 14, 2016, and August 31, 2016. For this, we used a doubledifference relocation method to constrain high-resolution hypocenter locations by cross-correlation differential times as well as the NIED Hi-net catalog differential times. The sequence included two large events (on 14 April: M JMA 6.5 and on 16 April: M JMA 7.3) that occurred in a complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The 2016 Kumamoto crustal earthquake sequence occurred with a large inelastic strain‐rate (>10 ‐7 year ‐1 ; Matsumoto et al, ), resulting in an enormous number of aftershocks along the Futagawa and Hinagu active faults at a depth of ~17 km and under the Suizenji fault area at ~10 km (Goto et al, ; Yano & Matsubara, ). These seismotectonic features imply that the crustal materials are inelastic and deformation extends from near the surface down to several kilometers in the vicinity of faults.…”
Section: Discussionmentioning
confidence: 99%
“…The 2016 Kumamoto crustal earthquake sequence occurred with a large inelastic strain‐rate (>10 ‐7 year ‐1 ; Matsumoto et al, ), resulting in an enormous number of aftershocks along the Futagawa and Hinagu active faults at a depth of ~17 km and under the Suizenji fault area at ~10 km (Goto et al, ; Yano & Matsubara, ). These seismotectonic features imply that the crustal materials are inelastic and deformation extends from near the surface down to several kilometers in the vicinity of faults.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one to four paleoseismic events prior to the 2016 earthquake in the past ∼10,000 years were detected on the Futagawa fault from trench excavation observations and radiocarbon dating results, and a recurrence interval of ∼2,000-4,000 years was inferred. On the other hand, Yano and Matsubara (2017) determined a dip of ∼75°NW for the Futagawa fault based on the locations of seismicity that occurred from 14 April to 31 August 2016. This steep dip also corresponds to the fault dip through the finite difference method using radon-222 (Rn) concentration data in soil gas obtained on survey lines mostly orthogonal to the fault strike (Koike et al, 2009).…”
Section: Geological Settingmentioning
confidence: 99%
“…During the earthquake, surface ruptures that were approximately 28 km long appeared along the ENE-WSWtrending Futagawa fault zone on the western side of Aso Volcano (Figure 2a). Large dextral slip with a maximum displacement of 2.2 m was measured throughout the central section of the rupture zone along the Futagawa fault, which is nearly vertical near the surface and dips northwestward at depth (Shirahama et al, 2016;Yano & Matsubara, 2017). Moya et al (2017) calculated the coseismic displacement along the Futagawa fault using a pair of digital surface models obtained from LiDAR data before and after the mainshock.…”
mentioning
confidence: 99%
“…The detailed spatial distribution of the Gyeongju earthquakes represents the occurrence of E1 and E2 on two parallel fault planes of F1 and F2, with an offset of 600-700 m. Complex fault systems with two or more parallel faults can also be found in other regions (Durá-Gómez & Talwani 2009;Rabak et al 2010;Yano & Matsubara 2017). Yano & Matsubara (2017) reported that part of the 2016 Kumamoto earthquake sequence was aligned on two vertical fault planes in the northeastern area of Mt Aso with two moderatesized aftershocks (M ≥ 5) located on either side of the fault plane. This is consistent with our results that major events in a sequence separately occurred on visually identified faults.…”
Section: Fault System Complexitymentioning
confidence: 99%